Le Krimi sous le Troisième Reich : une invention de l'étranger - Vincent Platini (Transatlantica)
This article deals with the specificity of the crime novel under the Third Reich and its relation to the Anglo-American genre, from an economic, ideological and formal perspective. As a marketable commodity, the so-called Krimi was informed by commercial as well as political imperatives. This logic granted it a small degree of freedom and placed it in competition with the foreign products that dominated the literary market. However, with the increasing totalitarianism of the regime, translated novels became scarcer and ideological pressures exerted themselves heavily on the Krimi. The crime novel then took on dictatorial forms, reflecting the changed conception of the law in the new Germany and contrasting with the English tradition of the genre. Although Nazi Krimis and American hard-boiled stories converged to a certain extent, the German products differed unmistakably in their opposition to the imagination prevalent in democratic countries. Nevertheless, despite ideological pressures, the Krimi never became entirely subservient to the regime : it continued to harbor foreign influences and, by launching into imaginary exiles, even managed to mock the power of Nazism.